Youth Responses to the Surveillance School: The Bifurcation of Antagonism and Confidence in Surveillance among Teenaged Students. (November 2019) - Adorjan, Michael; Ricciardelli, Rosemary
The recent rise of so-called 'surveillance schools' is often justified given the need to engender a safe and secure educational environment for students—a fusion of pedagogical and security motives. This article contributes knowledge regarding the attitudes and lived experiences of teenagers in response to school-based surveillance. Focus groups centre discussions on two areas: the effectiveness of policies regarding technology in the classroom as well as school-wide restrictions on Wi-Fi access and the effectiveness of surveillance technologies geared to actively monitor student online activities. We explore a bifurcation of attitudes revealing both resistance to surveillance school practices as well as strong support for monitoring technologies perceived to be effective in addressing cyber-risks like cyberbullying. Our findings point to the need for empirically assessing the contexts where support or antagonism towards surveillance occurs, suggesting neither isomorphic resistance nor wholescale acquiescence.